Evaluation of andrographis paniculata (hempedu bumi) extract formulation as an antifungal agent against superficial mycoses - Tuan Kub, Tuan Noorkorina (2018)
Superficial mycoses are commonly encountered fungal infections, which often present as skin lesion, itchiness, nail damage and hair loss. Although a number of antifungal agents are available at present, development of new classes of antifungal agents is limited. The increasing need for antifungal therapy and the emergence of antifungal resistance warranted the need for discovery of novel antifungal agents. Andrographis paniculata (AP), an ancient medicinal herb, is claimed to possess various pharmacological activities including antimicrobial activities. Therefore, the present study was embarked to evaluate the antifungal effect of AP extract and its formulations against selected fungal pathogens causing superficial mycoses. In the initial part of the study methanol, ethanol and aqueous extracts of AP, were tested for their effects on the growth of Trichophyton mentagrophyte, T. rubrum, T. interdigitale, Microsporum fulvum, M. nanum, M. gypseum, M. canis, Fusarium solani and Aspergillus fumigatus using disc diffusion and food poisoning method on potato dextrose agar. The extract which exhibited the best antifungal effect was formulated into cream and gel. The toxicity effects of AP extract were evaluated using mouse skin fibroblast cell lines (L929), brine shrimp and New Zealand White Rabbit. The stability of the gel and cream formulations were also evaluated. In an animal study, superficial fungal infection in a Sprague-Dawley rat model was established and the in vivo antifungal and wound healing effects of AP formulations against T. mentagrophyte, T. rubrum, T. interdigitale, M. gypseum and M. canis infections was examined. The chemical compounds of AP extract were also identified using phytochemical screening, HPLC and ATR-FTIR methods. AP crude extract showed activity against T. mentagrophyte, T. rubrum, T. interdigitale, M. fulvum, M. nanum, M. gypseum, and M. canis. Ethanol extracts of AP in gel formulation showed the best antifungal activity. The stability evaluation of the gel and cream formulations demonstrated the superiority of AP gel formulation. The toxicity evaluation demonstrated adequate safety of all forms of AP tested. The results of in vivo antifungal effect showed significant antifungal effects (p<0.01) in AP ethanol extract gel compared to negative control (untreated), in terms of the percentage of wound healing, wound size reduction and wound conditions scoring. Histopathological examination of the wound sections using haematoxylin-eosin (H&E) and Grocott-Gomori’s Methanamine Silver (GMS) staining showed eradication of fungal elements following AP ethanol extract gel treatment compared to untreated control. The chemical evaluation of AP extracts revealed the presence of andrographolide and neo-andrographolide content in methanol and ethanol extract, while ethanol extract showed the presence of saponins, flavonoids and tannins. AP has pronounced antifungal activity based on the demonstration of its effects in both in vitro and in vivo studies. Therefore, the findings in this study have provided the evidence for potential use of AP as a novel antifungal agent for superficial mycoses. Further laboratory and clinical studies are needed to ascertain the use of new AP formulation as an alternative treatment for superficial mycoses.